Preferential Riverine Export of Fine Volcanogenic Particles to the Southeast Australian Margin - Bayon, Germain; Douglas, Grant B.; Denton, Geoff J.; Monin, Laurence; De Deckker, Patrick (Frontiers in Marine Science, 2020)
We report on rare earth element and neodymium isotopic compositions in a series of grain-size fractions separated from river suspended matter in the Murray-Darling Basin (MDB) and a nearby marine sediment core (MD03-2607) offshore south-eastern Australia. This source-to-sink approach was used to further investigate the extent to which sediment sorting may control the geochemistry of suspended loads in rivers, and to provide constraints on the source of the detrital sediment material exported to the ocean. Our results provide further compelling evidence that significant size-dependent geochemical decoupling can occur in river systems, accounting here for Nd isotopic (Nd) differences of up to 8 epsilon-units between silt (>25µm) and colloidal (0.2-0.006 µm; 0.006-0.003 µm) fractions. All suspended particulate samples from the River Murray watershed display a trend towards more radiogenic (higher Nd) Nd signatures with decreasing grain-size, in addition to differing REE signatures, which collectively point towards a preferential volcanogenic origin for the fine-grained inorganic particles transported by MDB rivers. Furthermore, we show that the same river-borne volcanogenic material dominates in the fine-grained detrital fractions extracted from core MD03-2607 at the south-eastern Australian margin; a finding corroborated by REE signatures in a series of copepod faecal pellet separates from the same core. Collectively, our results suggest that river sediment discharge is accompanied by preferential export of fine-grained volcanogenic particles to the ocean. This potential source of bioavailable trace metals and nutrients in ocean surface waters could impact marine productivity.